Qualitative Traits and Body Condition Score (BCS) of Buffaloes in Mount Sangiang - Wandira, Ica Ayu; Sadia, I Nyoman; Dohi, Muhammad; Karni, Ine; Aminurrahman, Aminurrahman; Pertiwi, Eva Amalia; Nurjanah, Luluk lailatun (Jurnal Biologi Tropis, 2025)
Buffaloes in different regions of Indonesia exhibit unique physical characteristics influenced by genetics and environment, making them an important subject for morphological and condition assessments. This study aims to determine the qualitative traits and body condition score buffaloes in Mount Sangiang. This research is a descriptive observational study that involves both qualitative and/or quantitative sampling in the field, with a descriptive explanation using purposive sampling method. The study material includes 30 buffaloes, consisting of 15 males and 15 females, each of which was previously marked with identification tags. The results show that buffaloes in Mount Sangiang exhibit qualitative traits such as gray, black, and blonde hair colors; horn shapes of 'kerung' and 'baplang'; tail colors of black and brown; lower leg colors of white and pink; the presence of 1, 2, 3, and 4 whorls; flat and curved dorsal lines; and 2 white collar lines. The BCS for buffaloes in Mount Sangiang is 3 for male buffalo calf, young males, adult males, female buffalo calf, and heifers, while adult females have a BCS of 4.